EFEK POTENSIAL INSTRUMEN EVALUASI KOMPETENSI PEMODELAN MATEMATIS BAGI SISWA MENENGAH ATAS (JURNAL LEMMA, 2020)
The goal of this research is to know the potential effect of instrumen evaluation competence of mathematical modeling for senior high school students. This research is research and development based on the Borg and Gall steps. The subject of research is X-grade students MIA 3 SMA Negeri 7 Yogyakarta (main trial). Data collection techniques are conducted (a) walk through to know the validity of the instrument in content, construct, and language; (b) documentation to know the practicality of the questions; (c) tests and interviews were used to determine the potential effects of the 24-item multiple-choice PISA-type tools with 8 mathematical modeling competencies. The results showed that the potential effect of the mathematical modeling competency was quite good. This is demonstrated by the main test results indicating that 35.48% of students have high competence, and 64.52% have moderate competence.